Lethal dose, clinical signs, pathological changes and disease development of Streptococcus agalactiae following intraperitoneal exposure to Javanese medaka (Oryzias javanicus, Bleeker 1854) - Mastor, Siti Suhaiba (2018)
This study was conducted to determine the median lethal dose, clinical signs, pathological changes and disease development of Streptococcus agalactiae in Javanese medaka (Oryzias javanicus, Bleeker 1854) model, following intraperitoneal exposure. Javanese medaka was collected from estuary area of Sungai Pelek, Sepang, Selangor, and brought to the laboratory for quarantine and acclimatization. The fish were then challenged from 102 - 108 CFU/mlof virulent S. agalactiae via intraperitoneal injection. Mortalities and clinical signs were observed until 240 h post infection (hpi), while the dead fish were collected for bacterial isolation and histological analyses. Median lethal dose 50% (LD50) of S. agalactiae in Javanese medaka was determined at 5.3 × 102CFU/ml. Most of the infected fish showing lethargy, erratic swimming pattern, exophthalmia and necrosis at the injection site. The histopathological changes were mainly generalised congestion of the internal organs. Streptococcus agalactiae were successfully isolated from the dead fish. In the disease development studies, the number of Javanese medaka mortalities following infection by 103 CFU/ml of S. agalactiae was directly proportional with concentration of S. agalactiae in fish and severity of histopathological findings through 96 hpi. Clinical signs and histopathological assessment also showed that infected fish displayed similar findings compared to several the natural host of S. agalactiae. This study concluded that Javanese medaka was susceptible towards S. agalactiae infection and could be a potential alternative test organism for study of streptococcocis in fish.